The physiological basis of metabolic bone disease [ - Anderson, Paul H. , 1943-; Morris, Howard A.; Nordin, B. E. C. [ (Borje Edgar Christopher)] (CRC Press, 2014)
"Physiology and medicine are interrelated disciplines, and this is perhaps nowhere more apparent than in the field of mineral metabolism. This book presents information on the physiological principles regulating the response of mineral homeostasis on genetic, molecular, environmental, and nutritional factors. Chapters cover calcium and vitamin D nutrition, intestinal calcium absorption, plasma calcium homeostasis, renal handling of calcium, calcium sensing receptors, plasma phosphate homeostasis, endocrine actions of vitamin D, parathyroid hormone, calcitonin, and the calcification process"